The Influence of Organizational DNA on Employee Task Performance (Study Case: PT. Wijaya Karya Komponen Beton) (The Indonesian Journal of Business Administration, 2021)
Every company wanted to be a resilient/agile company, or a type of company whose people and internal environment can adjust or flexible-enough to embrace change caused by uncertain external environment. The difference between those Agile and those which not is simply from their internal capability to execute the strategy as the execution and implementation of the strategy by the company determines whether or not the company's business targets are achieved.One of the causes of inhibition of strategy execution and implementation is the presence of dysfunctionality in strategy execution process. It makes Employee Task Performance or the ability of a person as an individual or in a group to do their daily work is ineffective and influence overall company performance.The potential dysfunctional in the Employee Task Performance can be influenced byOrganizational DNA or simply company’s “surroundings” environment such as how the Structure supports daily business operational, is the Information is available and accessible for those whom needed, how decision-right is effectively taken, and how policy/system/practice are act as MotivatorPT. Wijaya Karya Komponen Beton (WIKA-KOBE) is one of the companies within developing and growing Indonesia’s precast concrete industry. The potential problem with them is they are often find themselves struggling categorized as “Healthy” in Financial Aspects one of indicator performance aspects in accordance of Decree of the Minister of State-Owned Enterprises No.Kep 100/MBU/2002 or one of standard indicator used to measures company performance. While they are often categorized as “Healthy” in other two categories Administration and Operational Aspects.The research has found that WIKA-KOBE is categorized as a “Just-in-time” company according to its Organizational DNA. In conclusion, WIKA-KOBE is included in the category of company that have great potential to be able to minimize dysfunctions that prevent their employee perform their task effectively and achieving their annual revenue targets. Developing recommendations and implementation plans that focus on every building block is required. Keywords: Organizational DNA, Dysfunctional, Employee Task Performance, Strategy Execution